The Gibeonites, the Nethinim and the Sons of Solomon's Servants - Haran, Menaḥem (Vetus Testamentum, 1961)
The aim of this article is to assemble the main features of the history of a Canaanite community whose fate was bound up with that of Israel. This community first emerges during the wars of Canaan, and disappears in the obscure period after Nehemiah. Its life-span thus virtually coincides with the history of Biblical Israel. During this long period the nature of the community in question underwent profound changes; nevertheless, it can be shown that its history forms a continuous whole which throws light on some social processes at work in Israel during the Biblical period. In this history, the following three main turning-points can be distinguished: Joshua's wars, the reign of Solomon, and the Return from Exile. Each of these turning-points marks a social and juridical change in the status of the community, as will be shown in the following pages.